Microgreens: A New Specialty Crop - Danielle D. Treadwell; Robert Hochmuth; Linda Landrum; Wanda Laughlin (EDIS, 2010)
HS1164, a 3-page illustrated fact sheet by Danielle D. Treadwell, Robert Hochmuth, Linda Landrum, and Wanda Laughlin, provides an overview of this new type of market crop and its production. Includes references. Published by the UF Department of Horticultural Sciences, April 2010.